Targeting of plant pattern recognition receptor-triggered immunity by bacterial type-III secretion system effectors. (February 2015) - Macho, Alberto P; Zipfel, Cyril
Highlights: Type-III effectors (T3Es) suppress plant immunity using multiple strategies. PRR-triggered immunity is redundantly targeted by multiple T3Es from a single bacterial strain. A single T3E can have multiple plant targets. A given immune component can be targeted by multiple T3Es. The study of T3Es reveals important immune components and unique biochemical processes. Abstract : During infection, microbes are detected by surface-localized pattern recognition receptors (PRRs), leading to an innate immune response that prevents microbial ingress. Therefore, successful pathogens must evade or inhibit PRR-triggered immunity to cause disease. In the past decade, a number of type-III secretion system effector (T3Es) proteins from plant pathogenic bacteria have been shown to suppress this layer of innate immunity. More recently, the detailed mechanisms of action have been defined for several of these effectors. Interestingly, effectors display a wide array of virulence targets, being able to prevent activation of immune receptors and to hijack immune signaling pathways. Besides being a fascinating example of pathogen-host co-evolution, effectors have also emerged as valuable tools to dissect important biological processes in host cells.